Consumer behavior - Hoyer, Wayne D. (South-Western Cengage Learning, 2013)
This book combines a foundation in key concepts from marketing, psychology, sociology, and anthropology with a highly practical focus on real-world applications for today's business environment. The new edition of this text incorporates the latest cutting-edge research and current business practices, including extensive coverage of social media influences, increased consumer power, emerging neuroscience findings, and emotion in consumer decision making. In addition, it includes an increased emphasis on social responsibility and ethics in marketing. With even more real-world examples and application exercises, including new opening examples and closing cases in every chapter, this book provides a thorough, engaging and enjoyable guide to this essential subject, enabling students and professionals alike to master the skills they need to succeed.